Pattern recognition and classification in time series data - Volna, Eva 1961-; Kotyrba, Martin 1984-; Janosek, Michal 1981- (Advances in computational intelligence and robotics (ACIR) book series, 2017)
This book focuses on intelligent methods and techniques for recognizing and storing dynamic patterns, emphasizing topics related to artificial intelligence, pattern management, and algorithm development in addition to practical examples and applications